Serial block‐face scanning electron microscopy of erythrocytes protruding through the human placental syncytiotrophoblast. Issue 4 (17th July 2017) - Palaiologou, Eleni; Goggin, Patricia; Chatelet, David S.; Lofthouse, Emma M.; Torrens, Christopher; Sengers, Bram G.; Cleal, Jane K.; Page, Anton; Lewis, Rohan M.
Abstract: The syncytiotrophoblast forms a continuous barrier between the maternal and fetal circulations. Here we present a serial block‐face scanning electron microscopy (SBFSEM) study, based on a single image stack, showing pooling of fetal blood underneath a region of stretched syncytiotrophoblast that has become detached from the basement membrane. Erythrocytes are protruding from discrete holes in the syncytiotrophoblast suggesting that, under specific circumstances, the syncytiotrophoblast may be permeable to fetal cells. This observation represents a pathological process but it poses questions about the physical properties and permeability of the syncytiotrophoblast and may represent an early stage in the formation of fibrin deposits in areas of syncytial denudation. This study also illustrates how the 3D images generated by SBFSEM allow the interpretation of structures that could not be understood from a single histological section.